A comprehensive guide to electric scooter regulation practices - Herrman, Mason (Kansas State University, 2019)
Electric scooters (“scooters”) are an exciting new member of the urban trend of micro-mobility, having appeared in cities as recently as 2018. Micro-mobility is an urban transportation solution that covers 5 miles or less; micro-mobility options previously included dockless bicycles, pedestrian-only areas, and autonomous vehicles (self-driving cars that do not require a human driver) until scooters burst on the scene in 2018. Micro-mobility options are meant to provide a convenient and cheap last mile option. Scooters provide just that. Scooters have been deployed by companies - more often than not - without any communication between cities on their implementation. By not communicating a plan for regulation with cities, many scooter programs failed or were rolled back due to temporary bans. While scooters may be a viable part of the micro-mobility solution, they conversely present as many issues as they do solutions. The issues that scooters unintentionally brought with them to cities included safety, liability, operational questions, and infrastructure questions. A lack of data and scholarly research on scooters compounded these issues. The purpose of this research is to help cities mitigate these issues and answer any questions related to scooter implementation with a thorough understanding of scooter regulations. This research is designed to provide cities a range of practices for scooter regulations without elevating any regulatory practice as best. Ultimately, this research can be used as a guide for cities when signing an agreement with a scooter company. To determine the range of regulatory practices for cities, a process of documentation review of scooter program precedent across 50 cities in the United States was undertaken. The programs that were reviewed in this study were exclusive relationships between cities and companies. From this documentation review emerged three core requirements for scooter operations; legal, operational, and financial. Each requirement is comprised of specific components. With this range of practices for the legal, operational, and financial requirements for successful scooter operations, a city should be more than prepared to properly regulate and allow scooters in their city.
Keywords: Electric scooter; Electric scooter regulations; Electric scooter legal; Electric scooter financial; Electric scooter operations; Electric scooter precedent